(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In wireless communication the goal is to transferred error free signal. The big amount of datasignal is moved over the channel. The impact on datasignal caused as a result of the Doppler’s impact and also fading in mobile wireless, due to which the inter provider disturbance as well as inter symbol interference is taken place in the signal which is sent. This regular difficulty happens in the wireless system. The method needed to oppose in multipath transmission to lessen the above trouble. This paper provides an overview of multipath propagation in wireless communication channel.